Double-layer omics analysis of castration- and X-ray-resistant prostate cancer cells. (20th May 2022) - Iwanaga, Mototaro; Kawamura, Hidemasa; Kubo, Nobuteru; Mizukami, Tatsuji; Oike, Takahiro; Sato, Hiro; Miyazawa, Yoshiyuki; Sekine, Yoshitaka; Kawabata-Iwakawa, Reika; Nishiyama, Masahiko; Ohno, Tatsuya; Nakano, Takashi
Abstract: Castration-resistant prostate cancer shows resistance to not only androgen deprivation therapy (ADT) but also X-ray therapy. On the other hand, carbon ion beams have a high biological effect and are used for various cancers showing resistance to X-ray therapy. The purposes of this study are to clarify the difference in the sensitivity of Castration-resistant prostate cancer to X-ray and carbon ion beams and to elucidate the mechanism. The androgen-insensitive prostate cancer cell line LNCaP-LA established by culturing the androgen-sensitive prostate cancer cell line LNCaP for 2 years in androgen-free medium was used for this study. First, colony formation assays were performed to investigate its sensitivity to X-ray and carbon ion beams. Next, DNA mutation analysis on 409 cancer-related genes and comprehensive transcriptome analysis (RNA-seq) were performed with a next-generation sequencer. Lethal dose 50 values of X-rays for LNCaP and LNCaP-LA were 1.4 Gy and 2.8 Gy, respectively ( P  < 0.01). The Lethal dose 50 values of carbon ion beams were 0.9 Gy and 0.7 Gy, respectively ( P  = 0.09). On DNA mutation analysis, AR mutation was observed specifically in LNCaP-LA. From RNA-seq, 181 genes were identified as differentially expressed genes (DEGs; FDR <0.10, P  < 0.00076) between LNCaP and LNCaP-LA. Function analysis suggested that cell death was suppressed in LNCaP-LA, and pathway analysis suggested that the NRF2-pathway involved in intracellular oxidative stress prevention was activated in LNCaP-LA. LNCaP-LA showed X-ray resistance compared to LNCaP and sensitivity to carbon ion beams. The AR mutation and the NRF2-pathway were suggested as causes of resistance.